#TITLE_ALTERNATIVE# - YAHYA, ARFASYAD
The sea surface height variation is affected by the gravitation of the objects in outer space especially Moon and Sun. This will occur the tidal force that makes the sea surface position dynamics. To know how much is the tidal force by doing the tidal observation in certain interval of time. The tidal data can be used to determine the sea surface trend (variation of sea surface position model) which is applicated in the lowest sea surface prediction (LAT).